Disease Impact, Diagnostic Delay, and Unmet Medical Needs of Patients With Cholinergic Urticaria in German-Speaking Countries - Altrichter, Sabine; Mellerowicz, Emilia; Terhorst-Molawi, Dorothea; Grekowitz, Eva; Weller, Karsten; Maurer, Marcus (Frontiers in Allergy, 2022)
Background Cholinergic urticaria (CholU) is a common type of chronic inducible urticaria. Little is known about the burden of the disease and its unmet medical needs. Aim To characterize the unmet medical needs of patients with CholU. Methods Patients with CholU (n = 111) took part in a German online survey that assessed their symptoms, diagnostic delay, impact on daily life, quality of life (QoL), and their experience with physician care. Results Virtually all patients reported typical signs and symptoms of CholU, i.e., whealing (93.7%) and itching (91.9%), in response to typical trigger situations, such as physical activity, passive warming, or stress. Despite this, patients reported a marked diagnostic delay of 30.2 months (range from 0 to 279 months). Only 38% of the patients received a blood examination, and only 16% underwent provocation testing for diagnosing CholU, as recommended by the international guidelines. Physician contacts were common, but patient satisfaction with their disease management was low. In total, 90.1% of the patients stated to have an uncontrolled disease, resulting in a strong impact on their everyday activities, sleep, and QoL. Conclusion Patients with CholU exhibit many important unmet needs, and improvement in the diagnostic workup and patient care is needed, as are better treatment options.